Selenium nanoparticles inhibit Staphylococcus aureus-induced nosocomial infection, cell death and biofilm formation - Ohood A. Radhi; Intisar Albandar; Kawther Alqaseer; Wijdan D. Shnain (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Staphylococcus aureus that is a major health problem in hospitals, recognized as the greatest important nosocomial pathogen and usually causing postoperative wound infections. Antibiotic resistance by Staphylococcus aureus has developed to be common, and resistance to almost all antibiotics has been found among the most strains of this pathogen. Biofilms are generally more resistant to both host’s defense mechanisms and to antibiotics than planktonic unicellular microbes. Therefore, it is increasingly recognized as important health problem for patients with microbial infections. Moreover, Staphylococcal diseases has found to be connected with programmed cell death in order to cause numerous diseases in human hosts. All that made Staphylococcus aureus infections are hard to treat. Selenium has been examined for numerous medical applications and evidence suggested that Staphylococcus aureus growth can be inhibited in the presence of selenium nanoparticles. Objectives: The specific objective of this study therefore was to investigate the prevalence, antimicrobial susceptibility patterns and associated risk factors of Staphylococcus aureus in patients with surgical site infections and burns infection. In addition to confirm that selenium nanoparticles may be used to effectively prevent and treat Staphylococcus aureus infections and thus should be further studied for such applications. Methods: A cross-sectional study was conducted from January 1, 2022 to December 30, 2022 among patients with surgical site infections and burns infection at Al- Najaf city hospitals in Iraq country. A total of 275 Staphylococcus aureus isolates were recovered from hospital patients with postoperative wound infection or burns infection isolation and identification were based on standard bacteriological and biochemical criteria. Biofilms formation in vitro was carried out by microtiter plate spectrophotometric technique. Through using the standard disc diffusion technique, isolated strains of Staphylococcus aureus were tested for antibiotic susceptibility patterns. Host cell killing by Staphylococcus aureus was assayed by using florescent microscopy. Finally, selenium nanoparticles to inhibit bacteria were tested by measuring the sizes of the inhibition zone for bacterial growth.Results: Of the 630 surgical patients who resident in Al- Najaf city hospitals and who had developed surgical site infection, Staphylococcus aureus was isolated from 275 (43.6%) cases. The results show that most Staphylococcus isolates were resistant to most antibiotics and have ability for biofilms formation and inducing host cells kill. Results of this study also provided that strongly inhibited growth of Staphylococcus aureus in the presence of selenium nanoparticles after 24 hours at 10, 20, 40 and 80 μg/ml. Conclusion: The incidence of Staphylococcus aureus infection in surgical and burn wards of AlNajaf city hospitals in Iraq country was found to be high. In addition, most isolates were extremely resistant to major antimicrobial agents and has ability for inducing biofilms formation as well as host cells kill. Moreover, this study suggests that selenium nanoparticles may be used to effectively prevent and treat Staphylococcus aureus infections and thus should be further studied for such applications.